1994
DOI: 10.1002/ijc.2910560214
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perfusion of mouse tumours after photodynamic therapy

Abstract: The influence of photodynamic therapy (PDT) on vascular perfusion was investigated in 2 s.c. mouse tumours, a radiation-induced fibrosarcoma (RIF I) and a squamous-cell carcinoma (SCCVII). The 86Rb extraction technique was used to measure changes in perfusion relative to cardiac output at various intervals after interstitial PDT. Control groups showed that vascular perfusion in the RIF I tumours decreased with increasing tumour size. For both tumours, of constant size, vascular perfusion decreased to less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Consistent with the above observations, no differences were found in tumour perfusion after high-or low-fluence-rate PDT. In both cases, tumour perfusion progressively decreased with time after treatment as has been described by others (Roberts et al, 1994;van Geel et al, 1994van Geel et al, , 1996. However, marked differences were found in cutaneous perfusion.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the above observations, no differences were found in tumour perfusion after high-or low-fluence-rate PDT. In both cases, tumour perfusion progressively decreased with time after treatment as has been described by others (Roberts et al, 1994;van Geel et al, 1994van Geel et al, , 1996. However, marked differences were found in cutaneous perfusion.…”
Section: Discussionsupporting
confidence: 81%
“…Previously published Photofrin data (Baas et al, 1994) for regrowth time after PDT alone (--) or with MMC (-) are also indicated by the dashed lines. The data for m-THPC PDT were previously published (Van Geel et al, 1994 …”
Section: Resultsmentioning
confidence: 99%
“…This difference may be due to the higher light dose (400 J cm-') required for effective tumour treatment with Photofrin-mediated PDT. These light doses require 68 min for delivery, by which time vascular perfusion probably inhibits the access of MMC into the tumour (Van Geel et al, 1994 …”
Section: Resultsmentioning
confidence: 99%
“…In addition to tumour cell-directed necrosis induced by PDT, HPD additionally accumulates in endothelial cells (Leunig et al, 1994), allowing destruction of the tumour vascular system (van Geel et al, 1994).…”
mentioning
confidence: 99%